Technological Prospection about Active Food Packaging - Nascimento, Sara Santos (2021)
Active packaging is a tool used by the food industry to maintain quality and increase the useful life of its products.  The analysis of patents and scientific articles related to this topic is essential to outline the profile of scientific productions and the generation of new products. This research was carried out spanning the period from 2011 to 2020 on the Scopus, Web of science, Science direct and Scielo databases. Technological prospection encompassed the Espacenet and Wipo databases, using the keywords “active packaging” and “active packaging food”, evaluating year of publication, location and area/category. USA. China and Spain had the highest number of articles publications, respectively, with the USA being the largest patent applicant. Despite the existence of several products on the international market with this technology, many publications were found, indicating that there is competitiveness problem and the need for development of new technologies.